Decoding the future of human resource: How human resource analytics revolutionise the organisational landscape - Ahmad Hafizi, Ahmad Giran; Puteri Fadzline, Muhamad Tamyez; Muhammad Ashraf, Fauzi; Nor Faradilla, Mohamed Idris; Madhavkumar, Vandana (Penerbit Universiti Malaysia Pahang, 2024)
Technological advances and digitalisation have revolutionised human resource management (HRM) by increasing the quantity of workforce data and widening its access to facilitate decision-making in businesses. This study aims to provide an in-depth understanding of big data analysis (BDA) by evaluating the current and future trends in human resource (HR) analytics through bibliometric analysis. The findings revealed significant research clusters on the knowledge structure and mapping of research streams in HR analytics. Several challenges in BDA application and firm performances were also identified, indicating its current and future trends in HR analytics. Implications for the new HRM landscape include the benefits and risks of using HR analytics tools that organisations must carefully monitor. Moreover, HR practitioners must understand the organisation's business needs and goals, analyse high-quality data that are relevant to the specific problem or question being addressed, and possess the technical skills and resources to implement and use HR analytics effectively.